The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pssb.201046402
|View full text |Cite
|
Sign up to set email alerts
|

Weak ferromagnetism in cobalt oxalate crystals

Abstract: Microcrystals of diaquocobalt(II) oxalate have been synthesized by the coprecipitation reaction of aqueous solutions of Cobalt (II) bromide and oxalic acid. Chemical analysis and thermal experiments revealed that there is only one phase present. X-ray powder diffraction studies show that this compound is orthorhombic with space group Cccm. Molar susceptibility versus temperature measurements show the existence of an antiferromagnetic ordering, however, the hysteresis measured in magnetization measurements as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…To better elucidate the thermal behaviour of the complexes, a graph of the weight difference for consecutive rows against the temperature was plotted (Figure 7). The thermograms of four of the complexes (MC 2 O 4 ⋅ H 2 O, where M = Fe 2+ , Co 2+ , Ni 2+ , and Zn 2+ ) show two well defined steps of weight loss in agreement with reports in literature [24,28,31]. The first weight loss for FeC 2 O 4 ⋅ H 2 O (20.9%) occurs in the range 170-218 ∘ C. This is attributed to the elimination of two molecules of water of crystallization according to the theoretical value (19.69%).…”
Section: X-ray Diffractionsupporting
confidence: 89%
See 2 more Smart Citations
“…To better elucidate the thermal behaviour of the complexes, a graph of the weight difference for consecutive rows against the temperature was plotted (Figure 7). The thermograms of four of the complexes (MC 2 O 4 ⋅ H 2 O, where M = Fe 2+ , Co 2+ , Ni 2+ , and Zn 2+ ) show two well defined steps of weight loss in agreement with reports in literature [24,28,31]. The first weight loss for FeC 2 O 4 ⋅ H 2 O (20.9%) occurs in the range 170-218 ∘ C. This is attributed to the elimination of two molecules of water of crystallization according to the theoretical value (19.69%).…”
Section: X-ray Diffractionsupporting
confidence: 89%
“…The XRD spectra of the cobalt complexes synthesised at different temperatures are shown in Figure 4. The observed XRD patterns are similar to that of the standard prepared from commercial oxalic acid as well as to those reported in the literature [20,24]. This indicates that cobalt oxalate dihydrate was obtained at the different synthesis temperatures.…”
Section: X-ray Diffractionsupporting
confidence: 87%
See 1 more Smart Citation
“…The % extraction values calculated using the ICP-OES analysis results of the solutions taken from the reactor at the end of the 3 hours experiment period are given in Table 3. When Table 3 [29]. The EDS analysis of the solid material includes the peaks of cobalt and oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…This uncompensated antiferromagnetism produces weak ferromagnetism (WF). Recently, investigations in the quasi-onedimensional magnetic compound β − CoC 2 O 4 · 2H 2 O [6] revealed that the intra and interchain magnetic interactions tilt the spins, distorting the antiferromagnetic order and producing the WF.…”
Section: Introductionmentioning
confidence: 99%